(untitled) (Global Journal of Medical Research, 2016)
Childbirth is a central event to human nature and one that has a great impact on the life of women and their families. Over the years, remarkable progresses were made in the safety and comfort of human labor and birth but there is also an increase in maternal as well as neonatal mortality. The DOH embarked on Essential Intrapartum and Newborn Care (EINC) to address neonatal deaths in the country. This descriptive correlation study was conducted to determine the extent of implementation of the EINC protocol in the three areas: labor room (LR), delivery room (DR), and Neonatal Intensive Care Unit (NICU) of the selected private and public hospitals in Iligan City, and the perceived barriers to its implementation. A sample of 62 staff nurses (86.5%) and midwives (14.5%) were purposively selected from two private hospitals and three public hospitals in Iligan City. A three-part structured questionnaire was utilized to carry out the rationale of the study. The results revealed that the staffs were generally applying the steps/procedures in the EINC protocol in their respective units.